Identifikasi Barang Bukti Percakapan Aplikasi Dual Apps Whatsapp Pada Ponsel Xiaomi Menggunakan Metode NIST Mobile Forensics - Dedy Hariyadi; Ike Yunia Pasa; Dedy Hariyadi (INTEK : Jurnal Informatika dan Teknologi Informasi, 2018)
Mobile Forensics is a scientific branch of Digital Forensics related to the handling of digital evidence on mobile devices. The growth of mobile devices technologies such as smartphones need quite unique and adaptive handling with technological developments. Technological innovations in mobile devices should be handled thoroughly. As an example of Dual Apps new features launched by Xiaomi also need to be identification of digital traces. Dual Apps feature allows 1 phone to have 2 accounts on 1 social media app. Using the NIST Mobile Forensics method to identify digital evidences left behind by the Dual Apps ecosystem.